(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Shunthyadi tailam, a classical Ayurvedic formulation as Nasya therapy mentioned in Ashtang hrudaya for therapeutic use in Bhrushakshava. Bhrushakshava can be compared to the acute phase of allergic rhinitis. This study focuses on its pharmaceutical preparation and analytical standardization, adhering to the guidelines of the Ayurvedic Pharmacopoeia of India. The formulation was subjected to organoleptic and physico-chemical evaluations to establish benchmark standards. Key parameters such as acid value, saponification value, iodine value, specific gravity and refractive index were analyzed. These findings provide a scientific foundation for future research and ensure the quality and consistency of Shunthyadi tailam in therapeutic applications.